GAME APPLICATIONS IN SPACE SHOOT USING MACROMEDIA FLASH MX VERSION 6.0 - Irwan Maulana; Rahayu Noveandini, SKom, MMSI Rahayu Noveandini, SKom, MMSI (Jurnal Sistem Informasi, 2007)
To study computer science in order not to get bored in a single study should beconducted by one game or entertainment games. Making a game or that game couldbe done in various ways. Here the authors use the program Macromedia Flash MX tocreate a battle game applications in space flight is running on the computer.Application Program In Space Shoot game created using Macromedia Flash MXprogram is a computer game application program that displays the object plane whichcan move and fired a laser from the barrel of his gun by the players. The task ofprotecting the earth from the players every enemy attack space.Use of Libraries and ActionSript in making this program a facility has been providedby Macromedia Flash MX that serves to facilitate the creation and organization of thefiles needed for movie-making game Shoot In Space.